2017
DOI: 10.7554/elife.30483
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of the bifunctional secretin complex of Thermus thermophilus

Abstract: Secretins form multimeric channels across the outer membrane of Gram-negative bacteria that mediate the import or export of substrates and/or extrusion of type IV pili. The secretin complex of Thermus thermophilus is an oligomer of the 757-residue PilQ protein, essential for DNA uptake and pilus extrusion. Here, we present the cryo-EM structure of this bifunctional complex at a resolution of ~7 Å using a new reconstruction protocol. Thirteen protomers form a large periplasmic domain of six stacked rings and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 64 publications
1
24
0
1
Order By: Relevance
“…The structure of various T4P secretins has been examined [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] , including structures of PilQ from Neisseria meningitidis 45 , Pseudomonas aeruginosa 46 , and Thermus thermophilus 47 , although no work has provided high-resolution details sufficient to model the passage of DNA or to design inhibitors of this potential drug target. Thus, structural information about the T4P secretins has mainly been inferred from the related but distinct T2SS and T3SS secretins [55][56][57][58][59][60][61] .…”
mentioning
confidence: 99%
“…The structure of various T4P secretins has been examined [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] , including structures of PilQ from Neisseria meningitidis 45 , Pseudomonas aeruginosa 46 , and Thermus thermophilus 47 , although no work has provided high-resolution details sufficient to model the passage of DNA or to design inhibitors of this potential drug target. Thus, structural information about the T4P secretins has mainly been inferred from the related but distinct T2SS and T3SS secretins [55][56][57][58][59][60][61] .…”
mentioning
confidence: 99%
“…Two retraction ATPases, PilT1 and PilT2, are essential for T4P depolymerisation 8,9 . T4P are extruded through the outer membrane secretin PilQ [10][11][12][13] . Recently, it has been suggested that expression of the T. thermophilus major pilin PilA4 is temperature dependent, leading to hyperpiliation at suboptimal growth temperatures 14 .…”
mentioning
confidence: 99%
“…N0 in EpsD from the T2SS of V. vulnificus was not traceable in the cryo‐EM map due to flexibility and is thus indicated in blue. Numbers indicate domain delimitations, as indicated in the publications describing the structures in Figure …”
Section: Introductionmentioning
confidence: 99%